Structural evolution and reaction pathways of hematite reduction by biomass-lignin derived bio-coke - Kefeng Wu; Lichao Ge; Lei Yao; Chunxia Yang; Nai Rong; Yanquan Liu; Yang Wang; Chang Xu (Bioresource Technology, 2026)

Carbon dot-based catalytic materials: From photo/electrocatalysis to nanozyme activity - Pei-De Zhu; Chang Liu; Hui Wang; Rong-Yu Yao; Ling-Rui Sun; Xin-Ru Xu; Jing-Wen Jiang; Ying-Sheng Xu; Kun-Peng Lin; Jia-Xing Wu (Journal of Environmental Chemical Engineering, 2026)

Persistence of a high-risk opportunistic pathogen amid compartment-resolved antibiotic resistance attenuation in acute shock-loaded micro-wetlands - Rong-min Zhang; Zi-yao Liu; Hui-ting Chen; Xin-ce Yang; Liwei Shi; Yi-cheng Zhang; Xin-ting Li; Lin-lin Yang; Jing-yu Xu; Xin-lei Lian; Li Li; Xian-hui Huang; et al. (Journal of Environmental Chemical Engineering, 2026)

Anaerobic digestion of recalcitrant organics and emerging contaminants in pharmaceutical wastewater for carbon neutrality and bioresource recovery: A critical review - Xinru Niu; Tao Zhang; Yao Xu; Jiaxin Ou; Chengzhen Meng; Fan Li; Lan Tang; Yong Hu; Chao Rong; Dapeng Li; Zhe Kong (Bioresource Technology, 2026)

Fipronil and its metabolites in a tropical estuary: multi-compartment distribution, trophic transfer, and risk assessment - Yu-Han Xie; Can Huo; Zhi-Yan Wang; Shan-Shan Yao; Heng-Xiang Li; Yu Zhong; Xiao-Ping Huang; Xiang-Rong Xu (Marine Environmental Research, 2026)

Denitrification-enhanced anaerobic digestion for stable synergy of hydrolysis and methanogenesis of N, N-dimethylformamide by nitrate addition: Delayed stimulation effect for successful enrichment of functional microorganisms - Junjie Zhou; Zhihao Shi; Tao Zhang; Yao Xu; Yong Hu; Chao Rong; Dapeng Li; Yu-You Li; Zhe Kong (Environmental Research, 2026)

Flexural behavior of coarse aggregate-UHPC bridge slabs: A combined phase analysis and layered strength model approach - Qizhi Xu; Shimin Ding; Yan Tang; Jingquan Wang; Hui Rong; Yiming Yao (Engineering Structures, 2026)

Nitrogen enrichment alters the relationship between grassland biodiversity and ecosystem multifunctionality: A global meta-analysis - Tao Chang; Huakun Zhou; Hongye Su; Zeying Yao; Cuoji Peng; Hengkang Xu; Yuping Rong; Xinqing Shao (Agriculture, Ecosystems & Environment, 2026)

From scar walls to neural bridges: a convergent paradigm for next-generation spinal cord injury repair - Senyu Yao; Xu Huang; Jun Kang; Bin Liu; Limin Rong (Science Bulletin, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Successful establishment of denitrification-enhanced anaerobic digestion with nitrate as an exogenous stimulant for effective hydrolysis and methanogenesis of N, N-dimethylformamide-containing wastewater - Zhe Kong; Tao Zhang; Yao Xu; Yong Hu; Chao Rong; Yu-You Li (Water Research, 2026)

Release kinetics and environmental risks of TCPP from polyurethane foam microplastics: Insights from artificial seawater to natural estuarine water - Shan-Shan Yao; Yu-Han Xie; Zhi-Yan Wang; Shan Liu; Rui Hou; Lang Lin; Yu Zhong; Xiao-Ping Huang; Heng-Xiang Li; Xiang-Rong Xu (Environmental Pollution, 2026)

Bridging cortical intentions: brain–computer interfaces for spinal cord injury recovery - Xuantao Hu; Jiale He; Na Li; Jian Mo; Senyu Yao; Yubao Lu; Mudan Huang; Pan Jiang; Mao Pang; Lei He; Jin Gong; Zifeng Liu; et al. (Science Bulletin, 2026)

Thioredoxin PgTRX acts as a protein elicitor to suppress green mold in citrus fruit via modulation of glutathione metabolism - Rong Zhu; Ou Chen; Yao Xu; Rui Huang; Wenjun Wang; Jian Ming; Kaifang Zeng (Postharvest Biology and Technology, 2026)

Advances in natural biomacromolecule-based Janus materials: preparation, applications and future prospects in food science - Ying Xu; Xuan Tao; Liubin Li; Yao Chen; Rong He; Xingrong Ju; Zhigao Wang (Critical Reviews in Food Science and Nutrition, 2026)

Estimating soil moisture at farm scale with high spatial resolution: integrating remote sensing data, and machine learning - Di Wang; Shenhan Xu; Shuai Wang; Wenhui Liu; Nanjuan Zheng; Zhen Wang; Yao Rong; Chenglong Zhang; Chaozi Wang; Nigenare Amantai; Zailin Huo (Journal of Hydrology, 2026)

Total Saponins of Panax Notoginseng Leaves Modulate the "Microglial-NLRP3/Caspase-1" Axis associated with Gut Microbial/SCFAs Alterations: Correlative Insights into Cognitive Improvement in Senescence - Lan Sun; Jiarong Du; Yuan Xu; Shanshan Wang; Yao Zhang; Rong Yuan; You Lv; Longyan Ding; Yanling Jin; Yu Ren; Xiaoman LV; Jiali Yuan; et al. (Molecular Neurobiology, 2026)

Release kinetics and bioaccessibility of heavy metal from antifouling paint particles in simulated digestive fluids: An emerging threat to marine biota - Zhen-Liang Li; Ting-Ting Xu; Shan-Shan Yao; Heng-Xiang Li; Shan Liu; Rui Hou; Lang Lin; Zhi-Xin Ni; Qun Xie; Xiao-Ping Huang; Xiang-Rong Xu (Marine Pollution Bulletin, 2025)

Corrigendum to “Myosin heavy chain 9 is a critical host factor for Japanese encephalitis virus entry and replication in U251 cells” [Vet. Microbiol. 310 (2025) 110723] - Kui Xu; Yu-Ke Xu; Jia-Fei Zhan; Lei Yuan; Ya-Lan Feng; Rong Huang; Yung-Fu Chang; Zhuang Zhu; Xiao-Yao Yang; Li-Yao Deng; Yang Deng; Yang Ren; et al. (Veterinary Microbiology, 2025)

Interaction of secreted protein PgSLP and citrus calmodulin-like protein CsCML27/44 in fruit disease defense - Yao Xu; Ou Chen; Rong Zhu; Rui Huang; Jian Ming; Shixiang Yao; Kaifang Zeng (Postharvest Biology and Technology, 2025)

Myosin heavy chain 9 is a critical host factor for Japanese encephalitis virus entry and replication in U251 cells - Kui Xu; Yu-ke Xu; Jia-Fei Zhan; Lei Yuan; Ya-Lan Feng; Rong Huang; Yung-Fu Chang; Zhuang Zhu; Xiao-Yao Yang; Li-Yao Deng; Yang Deng; Yang Ren; et al. (Veterinary Microbiology, 2025)

A durable immuno-protective core-shell microgel for the enhanced pancreatic islet transplantation in diabetes therapy - Zeming Hu; Yang Luo; Muhammad Junaid; Rong Xu; Yaoqi Chen; Jie Yao; Renhao Ni; Tong Zhu; Hua Zhang; Huiqing Ding; Yabin Zhu (Chemical Engineering Journal, 2025)

Vanadium-cobalt oxide nanoflower catalyst for efficient and stable overall water splitting in alkaline and seawater electrolytes - Yong-qi Tian; Song-lin Xu; Jia Li; Shuang-shuang Zhang; Bo-yao Zhang; Rong-da Zhao; Fu-fa Wu; De-peng Zhao (Next Research, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Dynamic performance tests and multi-parametric refinement models of high-energy dissipation viscoelastic materials for seismic performance enhancement of engineering structures - Yao-Rong Dong; Zhao-Dong Xu; Lihua Zhu; Bao-Shun Wang; Yang Yang; Yu Cheng (Engineering Structures, 2025)

A novel multi-dimensional viscoelastic mitigation device: Shake table tests and numerical assessment of precast concrete sandwich wall panel structure - Jia-Xuan He; Zhao-Dong Xu; Zhong-Wei Hu; Lian-Yu Zhang; Qiang-Qiang Li; Yao-Rong Dong; Gabriele Milani (Engineering Structures, 2025)

Glycoside hydrolase PgGal31A inhibits citrus blue mold via modifying cell wall components - Rong Zhu; Ou Chen; Yao Xu; Jian Huang; Huali Wang; Lili Deng; Shixiang Yao; Lanhua Yi; Kaifang Zeng (Postharvest Biology and Technology, 2025)

Ant colony-inspired cooperative control of multi- magnetorheological dampers system for coupled vibration mitigation of spatial irregular structures - Yang Yang; Zhao-Dong Xu; Xing-Huai Huang; Yao-Rong Dong; Jun Dai; Yuan-Jin Li (Engineering Structures, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Horizontally oriented 2D skin structures on fiber interface for long-life flexible energy storage devices - Guangyu Fang; Xiaorui Ma; Rong Hu; Jiao Dai; Haoran Tian; Lin Li; Weilin Xu; Yonggang Yao; Jun Wan (Chemical Engineering Journal, 2025)

Optimizing nitrogen fertilization and irrigation strategies to balance agroecosystem services in the wheat-maize double cropping system: A 21-year field study - Xinyue Qu; Wei Yao; Huijia Ji; Yi Xu; Rong Jia; Xinjie Chen; Hongjun Li; Antonio Rafael Sánchez-Rodríguez; Yanjun Shen; Yadong Yang; Zhaohai Zeng; Huadong Zang (Field Crops Research, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Investigation of the effects of polyethylene microplastics at environmentally relevant concentrations on the plant-soil-microbiota system: A two-year field trial - Meiling Xu; Wenqian Ma; Yu Yao; Qiao Xu; Wenchao Du; Ying Yin; Rong Ji; Xiaozhi Wang; Hongyan Guo (Science of The Total Environment, 2024)

Phillyrin inhibits oxidative stress and neutrophil extracellular trap formation through the KEAP1/NRF2 pathway in gouty arthritis - Xiangfeng Xu; Yao Lu; Rong Shen; Li Fang (Immunologic Research, 2024)

Preparation of amino-functionalized CoAl-LDH/palygorskite hierarchical composites for CO2 capture - Shixiang Zuo; Min Sun; Weifeng Gong; Tongtong Tang; Xuhua Ye; Wenjie Liu; Ngie Hing Wong; Rong Xu; Guihua Chen; Chao Yao; Haoguan Gui; Xiazhang Li (Applied Clay Science, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Mitigation of malondialdehyde-induced protein lipoxidation by epicatechin in whey protein isolate - Wenhua Yao; Xingya Hao; Zhangjie Hu; Zhenghao Lian; Yue Cao; Rong Liu; Xiaoying Niu; Jun Xu; Qin Zhu (Food Chemistry, 2024)

Development of a loading and diagnostic system to study laboratory earthquakes - Rong Chen; Ying Xu; Xuan Li; Wei Yao; Sheng Huang; Qi Zhao (Bulletin of Engineering Geology and the Environment, 2024)

Viperin inhibits interferon-γ production to promote Mycobacterium tuberculosis survival by disrupting TBK1-IKKε-IRF3-axis and JAK-STAT signaling - Yao Liang; Yun Liang; Qi Wang; Qianna Li; Yingqi Huang; Rong Li; Xiaoxin Pan; Linmiao Lie; Hui Xu; Zhenyu Han; Honglin Liu; Qian Wen; et al. (Inflammation Research, 2024)
Objectives and design As an interferon-inducible protein, Viperin has broad-spectrum antiviral effects and regulation of host immune responses. We aim to investigate how Viperin regulates interferon-γ (IFN-γ) production in macrophages to control Mycobacterium tuberculosis (Mtb) infection. Methods We use Viperin deficient bone-marrow-derived macrophage (BMDM) to investigate the effects and machines of Viperin on Mtb infection. Results Viperin inhibited IFN-γ production in macrophages and in the lung of mice to promote Mtb survival. Further insight into the mechanisms of Viperin-mediated regulation of IFN-γ production revealed the role of TANK-binding kinase 1 (TBK1), the TAK1-dependent inhibition of NF-kappa B kinase-epsilon (IKKε), and interferon regulatory factor 3 (IRF3). Inhibition of the TBK1-IKKε-IRF3 axis restored IFN-γ production reduced by Viperin knockout in BMDM and suppressed intracellular Mtb survival. Moreover, Viperin deficiency activated the Janus kinase (JAK)-signal transducer and activator of transcription (STAT) signaling pathway, which promoted IFN-γ production and inhibited Mtb infection in BMDM. Additionally, a combination of the anti-TB drug INH treatment in the absence of Viperin resulted in further IFN-γ production and anti-TB effect. Conclusions This study highlights the involvement of TBK1-IKKε-IRF3 axis and JAK-STAT signaling pathways in Viperin-suppressed IFN-γ production in Mtb infected macrophages, and identifies a novel mechanism of Viperin on negatively regulating host immune response to Mtb infection.

Vertical distributions of lipid biomarkers in spring and summer in coastal regions of the East China Sea - Jiawei Gao; Shulan Xu; Rong Bi; Yaoyao Wang; Yang Ding; Hong Che; Jing Zhang; Peng Yao; Jie Shi; Meixun Zhao (Frontiers in Marine Science, 2024)
Lipid biomarkers are amongst the most widely used proxies in studies of the structure and functioning of marine food webs. However, vertical distributions of lipid biomarkers and their controlling mechanisms remain unclear, especially in highly dynamic coastal ecosystems. Here we tested vertical profiles of key lipid biomarkers (sterols and fatty acids) in suspended particles and their correlations with water masses in spring of 2017 and summer of 2018 in the Zhejiang coasts of the East China Sea. The Changjiang Diluted Water, the Taiwan Strait Water and the Kuroshio Subsurface Water showed strong contributions in the surface layer in spring, the surface layer in summer, and the deep layer in both seasons, respectively. Accordingly, lipid biomarker composition also varied between different water layers. Overall, lipid biomarker concentrations in the surface layer were around 2 ~ 7 times higher than those in the deep layer, indicating high phytoplankton biomass in the surface layer. The ratio of docosahexaenoic acid to eicosapentaenoic acid was also higher in the surface layer, especially in the south of our study region, suggesting high nutritional quality of particulate organic matters in the surface layer. Significant correlations between the depth profiles of lipid biomarkers and water masses suggested the control of water masses on lipid biomarker production. The distribution patterns of lipid biomarkers in our study are consistent with previous findings on zooplankton grazing and fish larvae, highlighting the significance of lipid biomarkers as trophic markers to study food web structure and functioning in highly dynamic coasts.

Pichia galeiformis-secreted protein PgSLP increases citrus fruit disease resistance by activating amino acid metabolism - Yao Xu; Ou Chen; Rong Zhu; Wenjun Wang; Lili Deng; Shixiang Yao; Kaifang Zeng (Postharvest Biology and Technology, 2024)

Cypermethrin induces Sertoli cell apoptosis through endoplasmic reticulum-mitochondrial coupling involving IP3R1-GRP75-VDAC1 - Rui Zhang; Xu-Xu Wang; Jia-fei Xie; Ting-ting Yao; Qian-wen Guo; Qi Wang; Zhen Ding; Jin-Peng Zhang; Mei-Rong Zhang; Li-Chun Xu (Reproductive Toxicology, 2024)

Performance enhancement of damaged RC structures with viscoelastic dampers: Damage assessment and optimal placement - Zhao-Dong Xu; Yuxuan Tao; Yun Yang; Yao-Rong Dong; Jin Duan; Shihua Li; Hao Wang; Shuai Wang (Soil Dynamics and Earthquake Engineering, 2024)

Anthropogenic disturbance driving population decline of a dominant tree in East Asia evergreen broadleaved forests over the last 11,000 years - Sheng‐Yuan Qin; Zheng‐Yu Zuo; Shuang‐Xiu Xu; Jie Liu; Feng‐Mao Yang; Ya‐Huang Luo; Jun‐Wei Ye; Yao Zhao; Jun Rong; Bing Liu; Peng‐Fei Ma; De‐Zhu Li (Conservation Biology, 2024)
Current biodiversity loss is generally considered to have been caused by anthropogenic disturbance, but it is unclear when anthropogenic activities began to affect biodiversity loss. One hypothesis suggests it began with the Industrial Revolution, whereas others propose that anthropogenic disturbance has been associated with biodiversity decline since the early Holocene. To test these hypotheses, we examined the unique vegetation of evergreen broadleaved forests (EBLFs) in East Asia, where humans have affected landscapes since the early Holocene. We adopted a genomic approach to infer the demographic history of a dominant tree ( Litsea elongata ) of EBLFs. We used Holocene temperature and anthropogenic disturbance factors to calculate the correlation between these variables and the historical effective population size of L. elongata with Spearman statistics and integrated the maximum‐entropy niche model to determine the impact of climate change and anthropogenic disturbance on fluctuation in its effective population size. We identified 9 well‐defined geographic clades for the populations of L. elongata . Based on the estimated historical population sizes of these clades, all the populations contracted, indicating persistent population decline over the last 11,000 years. Demographic history of L . elongata and human population change, change in cropland use, and change in irrigated rice area were significantly negatively correlated, whereas climate change in the Holocene was not correlated with demographic history. Our results support the early human impact hypothesis and provide comprehensive evidence that early anthropogenic disturbance may contribute to the current biodiversity crisis in East Asia.

Preparation of size-tunable Fe3O4 magnetic nanoporous carbon composites by MOF pyrolysis regulation for magnetic resonance sensing of aflatoxin B1 with excellent anti-matrix effect - Zhou Xu; Yanqiu Chen; Rong Wang; Maolong Chen; Jian Zhang; Yunhui Cheng; Bangben Yao; Li Yao; Jianguo Xu; Wei Chen (Food Chemistry, 2024)

Occurrence of liquid crystal monomers in indoor and outdoor air particle matters (PM10): Implications for human exposure indoors - Li-Li Yao; Jun-Li Wang; Rong-Fa Xu; Ming Zhu; Yan Ma; Bin Tang; Qi-Yuan Lu; Feng-Shan Cai; Xiao Yan; Jing Zheng; Yun-Jiang Yu (Science of The Total Environment, 2023)

Genome-wide discovery of Pichia galeiformis-secreted proteins and their induction of green mold resistance in citrus fruit - Ou Chen; Rong Zhu; Yao Xu; Shixiang Yao; Lanhua Yi; Kaifang Zeng (Postharvest Biology and Technology, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

The mechanisms of rapid seed germination in Caragana species adapted to low mean annual precipitation - Shi-Hua Qi; Guang-Qian Yao; Md. Mahadi Hasan; Hui Jiang; Xu-Dong Liu; Zheng-Fei Nie; Xia-Yi Zhang; Ya-Xian Du; Xue-Qian Tian; Feng-Ping Li; Xue-Rong Li; Xiang-Wen Fang (Trees, 2023)

A systematic analysis and evaluation of nutritional composition of 23 strains of marine microalgae commonly used in aquaculture - Jia-Xing Zhang; Zhao-Shou Ran; Hai-Xuan Xie; Fei Kong; Meng-Qi Zhang; Yao Zhou; Yan-Rong Li; Kai Liao; Xiao-Jun Yan; Ji-Lin Xu (Algal Research, 2023)

Neoproterozoic tungsten mineralization: Geology, chronology, and genesis of the Huashandong W deposit in northwestern Jiangxi, South China - Xu-Dong Huang; Di Huang; Jian-Jun Lu; Rong-Qing Zhang; Dong-Sheng Ma; Yao-Hui Jiang; Hao-Wen Chen; Jin-Xian Liu (Mineralium Deposita, 2023)

Shaking table tests and seismic assessment of a full-scale precast concrete sandwich wall panel structure with bolt connections - Jia-Xuan He; Zhao-Dong Xu; Lian-Yu Zhang; Zhi-Hua Lin; Zhong-Wei Hu; Qiang-Qiang Li; Yao-Rong Dong (Engineering Structures, 2023)

Dual-functional electrostatic self-assembly nanoparticles enable suppressed defects and improved charge transport in perovskite optoelectronic devices - Hu Zhang; Pengfei Xu; Zhiliang Chen; Hengkai Zhang; Wenlong Shao; Yanhui Li; Jianfeng Yao; Da Rong; Duanwangde Liu; Liangpan Yang; Siliang Wang; Pengbin Gui; et al. (Chemical Engineering Journal, 2023)

Research on Black-Box Modeling Prediction of USV Maneuvering Based on SSA-WLS-SVM - Lifei Song; Le Hao; Hao Tao; Chuanyi Xu; Rong Guo; Yi Li; Jianxi Yao (Journal of Marine Science and Engineering, 2023)
Unmanned surface vessels (USVs) are required to perform motion prediction during a task. This is essential for USVs, especially when conducting motion control, and this work has been proven to be complicated. In this paper, an off-line black box modeling method for USV maneuvering, the Sparrow search algorithm-based weighted-least-squares support vector machine (SSA-WLS-SVM) was proposed to recognize the motion model of a USV. Firstly, the construction of the USV test platform and the processing process of the experimental data were introduced, the correctness of the MMG model was verified using a comparison of the test data and the simulation results, and then the MMG model was used to produce sample data later. To improve the stability and robustness of LS-SVM, weighted least squares and SSA were introduced to perform the optimization of the parameters of the algorithm and its kernel function. Then, the random maneuvering dataset was obtained using simulation on the MMG model, which was then preprocessed and used for training the black-box model. To verify the generalization ability of the identified model, the black-box model was used for comparison analysis between motion prediction with the proposed model and maneuvering test on the USV platform in a scenario different from the training data.

Four new glycosides from Gerbera piloselloides - Ha Gao; Chen-Xu Zhao; Xin-Yao Luo; Jing-Rong Li; Xiao-Chuan Ye; Tao Zhang; Zhong-Mei Zou (Phytochemistry Letters, 2023)

Research on PID Parameter Tuning and Optimization Based on SAC-Auto for USV Path Following - Lifei Song; Chuanyi Xu; Le Hao; Jianxi Yao; Rong Guo (Journal of Marine Science and Engineering, 2022)
Unmanned surface vessels (USVs) are required to follow a path during a task. This is essential for the USV, especially when following a curvilinear path or considering the interference of waves, and this work has been proven to be complicated. In this paper, a PID parameter tuning and optimizing method based on deep reinforcement learning were proposed to control the USV heading. Firstly, the Abkowite dynamics model with three degrees of freedom (DOF) is established. Secondly, the guidance law on the line-of-sight (LOS) method and the USV heading control system of the PID controller are designed. To satisfy the time-varying demand of PID parameters for guiding control, especially when the USV moves in waves, the soft actor–critic auto (SAC-auto) method is presented to adjust the PID parameters automatically. Thirdly, the state, action, and reward functions of the agent are designed for training and learning. Finally, numerical simulations are performed, and the results validated the feasibility and validity of the feasibility and effectiveness of the proposed method.

Biocrust diazotrophs and bacteria rather than fungi are sensitive to chronic low N deposition - Xiaoying Rong; Xiaobing Zhou; Xiangzhen Li; Minjie Yao; Yongxing Lu; Peng Xu; Benfeng Yin; Yonggang Li; Zachary T. Aanderud; Yuanming Zhang (Environmental Microbiology, 2022)
Anthropogenic long‐term nitrogen (N) deposition may dramatically impact biocrusts due to the overarching N limitation of soil biota in deserts. Even low levels of N may reach a critical loading threshold altering biocrust constituents and function. To identify the impact of chronic and continuous low levels of N deposition on biocrusts, we created a realistic gradient mirroring anthropogenic N addition rate (2:1 NH 4 + : NO 3 − rates: 0.3, 0.5, 1.0, 1.5, 3 g N m −2 yr −1 ) and measured the response of bacteria and fungi within cyanobacterial‐dominated biocrusts over 8 years in a temperate desert, the Gurbantunggut Desert, China. We found that once N deposition reached 1.5 g N m −2 yr −1 biocrust bacterial communities, including diazotrophs, were altered while no such tipping point existed for fungi. Above the threshold, bacterial richness was enhanced, the relative abundance of Chloroflexi, FBP and Gemmatimonadetes was elevated, and diazotrophs shifted from being dominated by Nostocaceae and Scytonemataceae (Cyanobacteria) to free‐living Bradyrhizobiaceae (Alphaproteobacteria). Alternatively, the relative recovery of a few fungal species within the Lecanorales, Pleosporales and Verrucariales became either enriched or diminished due to N deposition. The chronic addition of N resulted in a dense and interconnected bacterial co‐occurrence network that accentuated a functional shift from networks dominated by phototrophic species within the Nostocaceae, Xenococcaceae, Phormidiaceae and Scytonemataceae (Cyanobacteria) to ammonia‐oxidizing species within the Nitrosomonadaceae (Betaproteobacteria) and nitrifying bacteria [i.e. Nitrospiraceae (Nitrospirae)]. Based on structural equation models, the effects of N additions on biocrust constituents were imposed through indirect effects on pH, soil electrical conductivity and ammonium concentrations. In summary, biocrust constituents are generally insensitive to chronic low levels of N depositions until rates reach above 1.5 g N m −2 yr −1 with diazotrophs being the most sensitive biocrust constituents followed by bacteria and finally fungi. Ultimately once the threshold is reached N deposition favours biocrust constituents utilizing inorganic N and other C sources over relying on phototrophic and/or N‐fixing cyanobacteria for C and N.

Neural Stem Cells Therapy for Ischemic Stroke: Progress and Challenges - Tong Zhao; Tongming Zhu; Liqian Xie; Yao Li; Rong Xie; Feng Xu; Hailiang Tang; Jianhong Zhu (Translational Stroke Research, 2022)

Recognition of the Multi-class Schizophrenia Based on the Resting-State EEG Network Topology - Fali Li; Lin Jiang; Yuanyuan Liao; Cunbo Li; Qi Zhang; Shu Zhang; Yangsong Zhang; Li Kang; Rong Li; Dezhong Yao; Gang Yin; Peng Xu; et al. (Brain Topography, 2022)

Influence of Notch Geometry on the Rock Fracture Toughness Measurement Using the ISRM Suggested Semi-Circular Bend (SCB) Method - Geli Zhao; Wei Yao; Xing Li; Ying Xu; Kaiwen Xia; Rong Chen (Rock Mechanics and Rock Engineering, 2022)

Effective adsorption of zeolite/carbon composite molecular sieve synthesized from spent bleaching earth - Shixiang Zuo; Xiaoman Cao; Wenjie Liu; Tianhua Liu; Xiazhang Li; Chao Yao; Rong Xu; Yongsheng Fu (Environmental Science and Pollution Research, 2022)

CARMA1 is required for Notch1-induced NF-κB activation in SIL-TAL1-negative T cell acute lymphoblastic leukemia - Ninghan Zhang; Jiawen Xu; Rong Wang; Ting Pan; Huanxin Zhang; Lingling Yin; Yao Yao; Linyan Xu; Shengyun Zhu; Qingyun Wu; Zhenyu Li; Xuejiao Liu; et al. (Journal of Molecular Medicine, 2021)

Consuming Different Structural Parts of Bamboo Induce Gut Microbiome Changes in Captive Giant Pandas - Zheng Yan; Qin Xu; Walter H. Hsu; Stephan Schmitz Esser; James Ayala; Rong Hou; Ying Yao; Dandan Jiang; Shibin Yuan; Hairui Wang (Current Microbiology, 2021)
Giant pandas consume different structural parts of bamboo (shoots, leaves and culms) during different seasons. Previous research showed different bamboo parts have varying nutritional content and that a long-term diet consisting of a single part of bamboo resulted in remarkable metabolic changes within captive giant pandas. However, the effects on the gut microbiome of giant pandas, as a result of a single bamboo part diet, have not been investigated. Here, we evaluated the changes in gut microbial communities based on single bamboo part diets and their potential implications by using 16S rRNA gene-based amplicon sequencing and metagenome shotgun sequencing. We found that the composition and function of the gut microbiome from captive giant pandas fed exclusively culms were significantly different from that of individuals fed shoots or leaves. During the culm feeding period, the gut microbiome showed strongest digestive capabilities for cellulose, hemicellulose and starch, and had the highest potential abilities for the biosynthesis of bile acids, fatty acids and amino acids. This suggests the microbiome aids in breaking down culm, which is more difficult for giant pandas to digest, as a means to compensate for the nutrient poor content of the culm. Genes related to fatty acid metabolism and tricarboxylic acid cycle enzymes were more abundant during the leaf stage diet than that in the shoot and culm stages. Thus, the microbiome may help giant pandas, which typically have low lipase levels, with fat digestion. These results illustrate that adaptive changes in the gut microbiome community and function may be an important mechanism to aid giant panda digestion when consuming different structural parts of bamboo.

Effects of drought and heat on the productivity and photosynthetic characteristics of alpine meadow plants on the Qinghai-Tibetan Plateau - Li Ma; Zhong-hua Zhang; Bu-qing Yao; Zhen Ma; Xiao-tao Huang; Bing-rong Zhou; Man-hou Xu; Jing Guo; Hua-kun Zhou (Journal of Mountain Science, 2021)

Construction and characterization of UAA-controlled recombinant Zika virus by genetic code expansion - Rong-Rong Zhang; Qing Ye; Xiao-Feng Li; Yong-Qiang Deng; Yan-Peng Xu; Xing-Yao Huang; Qing Xia; Cheng-Feng Qin (Science China Life Sciences, 2021)

Long-term impact of accidental pollution on the distribution and risks of metals and metalloids in the sediment of the Longjiang River, China - Qian-Li Ma; Ling-Ai Yao; Qing-Wei Guo; Guang-Jie Zhou; Rong-Chang Liang; Qiao-Li Fang; Zhen-Cheng Xu; Xue-Min Zhao (Environmental Science and Pollution Research, 2021)

Identification, functional characterization, and estrogen regulation on gonadotropin-releasing hormone in the spotted scat, Scatophagus argus - Hua-pu Chen; Xue-fan Cui; Yao-rong Wang; Zhi-yuan Li; Chang-xu Tian; Dong-neng Jiang; Chun-Hua Zhu; Yong Zhang; Shui-sheng Li; Guang-li Li (Fish Physiology and Biochemistry, 2020)

Roles of PTBP1 in alternative splicing, glycolysis, and oncogensis - Wei Zhu; Bo-lun Zhou; Li-juan Rong; Li Ye; Hong-juan Xu; Yao Zhou; Xue-jun Yan; Wei-dong Liu; Bin Zhu; Lei Wang; Xing-jun Jiang; Cai-ping Ren (Journal of Zhejiang University-SCIENCE B, 2020)

Associative learning is necessary for airborne pheromones to activate sexual arousal-linked brain areas of female rats - Yao-Hua Zhang; Ming-Ming Tang; Xiao Guo; Xiao-Rong Gao; Jin-Hua Zhang; Jian-Xu Zhang (Behavioral Ecology and Sociobiology, 2019)

Polymorphisms in the APOBEC3G gene of Chinese rhesus macaques affect resistance to ubiquitination and degradation mediated by HIV-2 Vif - Zhi-Qiang Jiang; Xu-Rong Yao; Hang Yu; Yue-Er Lu; Bei-Lei Liu; Feng-Liang Liu; Ya-Bin Jin; Min Zhuo; Yong-Tang Zheng; Fei Ling (Archives of Virology, 2019)

Genome-wide detection of additional fetal chromosomal abnormalities by cell-free DNA testing of 15,626 consecutive pregnant women - Hong Yao; Ya Gao; Jia Zhao; Rong Zhang; Huixin Xu; Huamei Hu; Yanmei Luo; Yuying Yuan; Meili Fu; Hongyun Zhang; Hui Jiang; Wei Wang; et al. (Science China Life Sciences, 2019)

Synthesis, antitumor evaluation and molecular docking study of a novel podophyllotoxin-lonidamine hybrid - Lei Zhang; Jie Zheng; Ying Rong; Chengli Yang; Li Long; Yingshu Xu; Yongzheng Chen; Jing Wang; Qizheng Yao (Medicinal Chemistry Research, 2018)

Assimilation of total lightning data using the three-dimensional variational method at convection-allowing resolution - Rong Zhang; Yijun Zhang; Liangtao Xu; Dong Zheng; Wen Yao (Journal of Meteorological Research, 2017)

Copper-modified palygorskite is effective in preventing and treating diarrhea caused by Salmonella typhimurium - Da-wei Yao; Ze-zhong Yu; Na Li; Yu-nong Hou; Jia-rong Xu; De-ji Yang (Journal of Zhejiang University-SCIENCE B, 2017)

MiR-219 Protects Against Seizure in the Kainic Acid Model of Epilepsy - Honghua Zheng; Rong Tang; Yi Yao; Zhilin Ji; Yuanyuan Cao; Zhaoji Liu; Feng Peng; Wenjie Wang; Dan Can; Huiqin Xing; Guojun Bu; Huaxi Xu; et al. (Molecular Neurobiology, 2016)

Geographical distribution and risk assessment of persistent organic pollutants in golden threads (Nemipterus virgatus) from the northern South China Sea - Qing Hao; Yu-Xin Sun; Xiang-Rong Xu; Zi-Wei Yao; You-Shao Wang; Zai-Wang Zhang; Xiao-Jun Luo; Bi-Xian Mai (Ecotoxicology, 2015)

Isolation from Proteus mirabilis of a novel class I 5-enopyruvylshikimate-3-phosphate synthase with glyphosate tolerance in transgenic Arabidopsis thaliana - Yong-Sheng Tian; Xiao-Fen Jin; Jing Xu; Jing Han; Wei Zhao; Xiao-Yan Fu; Ri-He Peng; Rong-Tan Wang; Quan-Hong Yao (Acta Physiologiae Plantarum, 2014)

Estimations of net primary productivity and evapotranspiration based on HJ-1A/B data in Jinggangshan city, China - Rong-hua Zhang; Rui Sun; Jun-ping Du; Ting-long Zhang; Yao Tang; Hong-wei Xu; Sheng-tian Yang; Wei-guo Jiang (Journal of Mountain Science, 2013)

Docking-based 3D-QSAR modeling of the inhibitors of IMP metallo-β-lactamase - Jiao Chen; Rong Yu; Bingzheng Shen; Yan Xu; Yifang Liu; Heng Zheng; Wenbing Yao (Medicinal Chemistry Research, 2013)

Expression of ethylene response genes during persimmon fruit astringency removal - Xue-ren Yin; Yan-na Shi; Ting Min; Zheng-rong Luo; Yun-cong Yao; Qian Xu; Ian Ferguson; Kun-song Chen (Planta, 2012)

Expression, purification, and activity assay of peptide deformylase from Escherichia coli and Staphylococcus aureus - Xuchun Che; Jinwei Hu; Lijuan Wang; Zhifeng Zhu; Qiong Xu; Junqiang Lv; Zheng Fu; Yajun Sun; Jia Sun; Gang Lin; Rong Lu; Zhi Yao (Molecular and Cellular Biochemistry, 2011)

Combination of Hyaluronic Acid Hydrogel Scaffold and PLGA Microspheres for Supporting Survival of Neural Stem Cells - Ying Wang; Yue Teng Wei; Zhao Hui Zu; Rong Kai Ju; Mu Yao Guo; Xiu Mei Wang; Qun Yuan Xu; Fu Zhai Cui (Pharmaceutical Research, 2011)

Over-expression of ThpI from Choristoneura fumiferana enhances tolerance to cold in Arabidopsis - Bo Zhu; Ai-Sheng Xiong; Ri-He Peng; Jing Xu; Xiao-Fen Jin; Xiu-Rong Meng; Quan-Hong Yao (Molecular Biology Reports, 2010)

Construction of a recombinant adenovirus vector expressing IL-18BP/IL-4 fusion gene and the anti-inflammatory effect induced by this gene on lipopolysaccharide-stimulated synovial fibroblasts - Hang-Ping Yao; Yun Qian; Xue-Ting Shao; Zhe-Rong Xu; Lin-Fang Cheng; Lei Feng; Nan-Ping Wu; Yun-Mei Yang (Inflammation Research, 2010)

Detection of survivin-expressing circulating cancer cells in the peripheral blood of patients with esophageal squamous cell carcinoma and its clinical significance - Mei Cao; Shang-Mian Yie; Sheng-Min Wu; Shu Chen; Be Lou; Xu He; Shang-Rong Ye; Ke Xie; Lin Rao; En Gao; Nai-Yao Ye (Clinical & Experimental Metastasis, 2009)

Vesicular stomatitis virus matrix protein gene enhances the antitumor effects of radiation via induction of apoptosis - Xiao-Bo Du; Jin-Yi Lang; Jian-Rong XU; You Lu; Yan-Jun Wen; Ju-Mei Zhao; Peng Diao; Zhi-Ping Yuan; Bin Yao; Ling-Yu Fan; Guo-Qing Wang; Li Liu; et al. (Apoptosis, 2008)

A new dibenzofuran and other constituents from Ligularia caloxantha , a chinese medicinal plant - Shu-Yun Shi; Ming-Hui Hu; Di-Yao Wu; Chang-Xin Zhou; Jian-Xia Mo; Juan-Hua Xu; Liu-Rong Chen; Hui Dou; Hua Peng; Xiao-Jiang Hao; Joachim Stöckigt; Yu Zhao (Natural Product Research, 2008)

A new phenolic glycoside from the stems of Hydnocarpus hainanensis - Hai-Ming Shi; Zhi-Rong Yao; Xing-Yun Chai; Zheng-Ren Xu; Yu-Hong Zhou; Jing Wen; Peng-Fei Tu (Natural Product Research, 2008)